Blood Profile and Performance of Native Chicken with Functional Feed - Iriyanti , Ning; Santosa, R. Singgih Sugeng; Rachmawati, W.S. (International Journal of Poultry Science, 2014)
Native chicken quality performances could be improved through high quality feed. Thus, their growth, body weight and egg production could be optimized. This research used 60 hens of 6 weeks old native chicken with functional feed which consist of : menhaden fish oil, N-3 isolate of Histamine Methyl Transferase enzyme producer, Lactobacillus and Bacillus sp. at 1:1. The treatment consisted of 4 groups i.e., R0 (control), R1 (the use of functional feed at 2.5%), R2 (the use of functional feed at 5.0%); R3 (the use of functional feed at 7.5%). These are arranged based on a Completely Randomized Design with 4 replications, each replications with 5 hens, respectively. The measured variables were blood profile (cholesterol, triglycerides, LDL, HDL, erythrocyt, leucocyte, hematocrit and plasma protein) and performance (feed consumption, lipid consumption, energy consumption and carcass percentage). The results revealed that functional feed has increased very significantly (p